2017
DOI: 10.1103/physreve.96.043201
|View full text |Cite
|
Sign up to set email alerts
|

Flame propagation in two-dimensional solids: Particle-resolved studies with complex plasmas

Abstract: Using two-dimensional (2D) complex plasmas as an experimental model system, particle-resolved studies of flame propagation in classical 2D solids are carried out. Combining experiments, theory, and molecular dynamics simulations, we demonstrate that the mode-coupling instability operating in 2D complex plasmas reveals all essential features of combustion, such as an activated heat release, two-zone structure of the self-similar temperature profile ("flame front"), as well as thermal expansion of the medium and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 54 publications
2
57
0
Order By: Relevance
“…Due to this damping, the peak structure of C t (q, ω) is lost and they become much broader. 24,74 In this case, an appropriate theoretical model taking into account competition between processes giving rise to mode propagation and damping is required.…”
Section: Important Remark On the Cutoff Wave Number Reconstructionmentioning
confidence: 99%
“…Due to this damping, the peak structure of C t (q, ω) is lost and they become much broader. 24,74 In this case, an appropriate theoretical model taking into account competition between processes giving rise to mode propagation and damping is required.…”
Section: Important Remark On the Cutoff Wave Number Reconstructionmentioning
confidence: 99%
“…colloids and complex plasmas). 9,[14][15][16][17] Our particular attention will be on the properties of collective modes in the system. Collective modes in 2D Coulomb solids are relatively well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, if a large enough melted spot is induced in the crystalline monolayer, the energy input from the localized fluid MCI will not be dissipated rapidly enough (through neutral damping and heat conduction in the crystal), causing a further increase in temperature triggering the expansion of the melted area in an uncontrolled positive feedback. This mechanism will lead to the total destruction of the crystalline monolayer as observed for regular MCI-induced melting of 2D complex plasma crystals [30][31][32]42,43]. Such an "explosive melting" of a 2D complex plasma crystal has been recently studied in detail by Yurchenko et al [43] and was found to be similar to impulsive spot heating and thermal explosion in ordinary matter [44].…”
Section: Discussionmentioning
confidence: 86%
“…In the presented experiments, the laser pulse created a localized melted spot in the crystal where the fluid MCI exists. The spatial temperature distribution T (r,t) in a continuous reactive medium, including damping, can be described by the following heat equation [43,44]:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation